Assessing downgrading of esophageal adenocarcinoma after neoadjuvant chemotherapy: a case report Indrasto Histopaedianto1, Adeodatus Yuda Handaya2*, Hendro Wartatmo2 - Adeodatus Yuda Handaya; Indrasto Histopaedianto; Hendro Wartatmo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
Esophageal carcinoma, squamous cell carcinoma, and adenocarcinoma, are a deadly serious malignancy. The delay in diagnosis due to the lack of specific symptoms in the early stages of the disease and the nature of esophageal cancer is very aggressive lead to a poor prognosis with a survival rate of small. Current management of esophageal cancer is recommended multimodal approach in the form of neoadjuvant chemotherapy or combined radiochemotherapy (CRT) and with surgery. In this article, multimodality treatment using chemotherapy and surgery on esophageal adenocarcinoma was reported. A 52-year-old male presented with a total obstruction of the esophagus and was planned to perform temporary gastrostomy for chemotherapy preparation. Gastrostomy found a solid and fixed tumor located in the gastroesophageal junction, with the size of 7 x 6 x 5 cm3. He underwent a chemotherapy using the regimen of 8 cycles paclitaxel without radiotherapy due to the long queue of radiotherapy schedule. After chemotherapy, we re-evaluated and planned to perform surgical removal of the tumor. During surgery, we found a total obstruction along with fibrosis of the esophagus but found no tumor/mass. We performed partial esophagectomy and end to side anastomosis using anastomosis end to side using the CDH25 circular stapler. Surgery was carried out by the thoracoabdominal approach. The patient was discharged on day 12 in a stable condition and was undergoing soft diet. We planned to evaluate the patient using Carcinoembryonic Antigen (CEA) test and Positron Emission Tomography (PET) scan. In conclusion, multimodality treatment using chemotherapy and surgery on a case of one-third distal esophageal adenocarcinoma provides good results.